2022
DOI: 10.1038/s41598-022-21520-w
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Gal/GalNAc lectin 2 (MGL2)+ peritoneal antigen presenting cells during Fasciola hepatica infection are essential for regulatory T cell induction

Abstract: Fasciola hepatica, one of the agents that causes fasciolosis, modulates the host immune system to allow parasite survival in the host. F. hepatica expresses carbohydrate-containing glycoconjugates that are decoded by C-type lectin receptors, such as Dectin-1, mannose receptor, DC-SIGN and MGL, that are mainly present on myeloid antigen presenting cells (APCs) and can mediate immunoregulatory properties on T cells. In particular, Macrophage Gal/GalNAc lectin 2 (MGL2) expands modified Th2 immune responses, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…61 Costa et al demonstrated that depletion of M2 macrophages was associated with partial resistance to infection and increase levels of Foxp3 + Treg. 62 In a subsequent study, this group demonstrated that splenic Tregs and production of heme-oxygenase-1 (HO-1) by peritoneal antigen presenting cells depends on IL-10 activity in Fasciola infected mice. Upregulation of HO-1 decreased the production of reactive oxygen and nitrogen species and increased the number of Treg.…”
Section: Chronic Phasementioning
confidence: 99%
“…61 Costa et al demonstrated that depletion of M2 macrophages was associated with partial resistance to infection and increase levels of Foxp3 + Treg. 62 In a subsequent study, this group demonstrated that splenic Tregs and production of heme-oxygenase-1 (HO-1) by peritoneal antigen presenting cells depends on IL-10 activity in Fasciola infected mice. Upregulation of HO-1 decreased the production of reactive oxygen and nitrogen species and increased the number of Treg.…”
Section: Chronic Phasementioning
confidence: 99%
“…In addition, the production of immunomodulatory molecules by mMGL2+ cells is associated with an increase in clinical symptoms and Treg expansion. Thus, it seems that MGL interactions are F. hepatica's strategy to escape host immune control [159].…”
Section: • Fasciola Hepaticamentioning
confidence: 99%
“…The role of MGL in immune regulation is not fully understood but appears to be highly dependent on the antigen structure. In some cases, glycotope interactions with MGL seem to facilitate immune escape of the pathogen via DC secretion of anti-inflammatory cytokines, such as interleukin-10 (IL-10), which reduces the glycolytic activity of DCs or abrogates the T helper 1/2 (Th1/2) type response in favor of regulatory T cells (Treg) or T helper 17 (Th17) type responses …”
Section: Introductionmentioning
confidence: 99%